'Designated areas' and the regulation of artisanal and small-scale mining. (November 2017) - Corbett, Tony; O'Faircheallaigh, Ciaran; Regan, Anthony
Abstract: Artisanal and small-scale mining (ASM) is an important and growing economic activity throughout the Global South. ASM can provide livelihoods where few alternative economic opportunities exist, but it can also cause significant social and environmental problems, creating a need for effective regulation. State authorities have, however, struggled to control an activity that is dynamic, has few barriers to entry, and often occurs in remote areas far from national capitals. One potential regulatory tool involves allocating land to establish 'designated areas' for ASM in order to contain operations within discrete zones, facilitating government control, managing relations between ASM and Large Scale Mining (LSM), and mitigating its negative effects. This article explains the rationale for use of designated areas, identifies key policy issues and choices involved in creating them, and provides examples of legislation providing for their establishment. It documents the fact that such provisions are in reality rarely implemented and that, where they are, they generally fail to meet demand for ASM land and are not effectively managed. It identifies a number of proximate causes for these failures, including competition for land, overlapping and ambiguous jurisdiction between different levels of government, resource constraints facing regulators and political ambivalence towards ASM at the national level. It argues that these causes can only be addressed by realigning the governance of land so as to give local and customary authorities a much greater role in land allocation and management, and if national governments overcome their ambivalence towards ASM and accept it as a vital source of economic activity that requires effective regulation.